Topical Calcipotriol Plus Imiquimod Immunotherapy for Nonkeratinocyte Skin Cancers - Marjan Azin; Kenneth H. Ngo; Jennet Hojanazarova; Shadmehr Demehri (Elsevier, 2023)
Nonkeratinocyte cutaneous malignancies, including breast cancer cutaneous metastasis and melanoma in situ, are often poor surgical candidates. Imiquimod (IMQ), a toll-like receptor 7 agonist that activates innate immunity in the skin, is used to treat these cutaneous malignancies. However, IMQ's modest effect on the activation of adaptive immunity limits its efficacy as a monotherapy. In this study, we demonstrate that topical TSLP cytokine inducers-calcipotriol and retinoic acid-synergize with IMQ to activate CD4+ T-cell immunity against nonkeratinocyte cutaneous malignancies. Topical calcipotriol plus IMQ treatment reduced breast tumor growth compared with calcipotriol or IMQ alone (P < 0.0001). Calcipotriol plus IMQ-mediated tumor suppression was associated with significant infiltration of CD4+ effector T cells in the tumor microenvironment. Notably, topical calcipotriol plus IMQ immunotherapy enabled immune checkpoint blockade therapy to effectively control immunologically cold breast tumors, which was associated with induction of CD4+ T-cell immunity. Topical treatment with calcipotriol plus IMQ and retinoic acid plus IMQ also blocked subcutaneous melanoma growth. These findings highlight the synergistic effect of topical TSLP induction in combination with innate immune cell activation as an effective immunotherapy for malignancies affecting the skin.